2001
DOI: 10.1211/0022357011775208
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of α-, γ- and δ-tocotrienols under different food status

Abstract: We have investigated the pharmacokinetics and bioavailability of alpha-, gamma- and delta-tocotrienols under fed and fasted conditions in eight healthy volunteers. The volunteers were administered a single oral dose of mixed tocotrienols (300 mg) under fed or fasted conditions. The bioavailability of tocotrienols under the two conditions was compared using the parameters peak plasma concentration (Cmax), time to reach peak plasma concentration (Tmax) and total area under the plasma concentration-time curve (AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
150
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 11 publications
9
150
0
Order By: Relevance
“…The lowest IC50 levels in breast cancer cells (McIntyre et al 2000) were obtained by means of days of in vitro exposure to concentrations of HM T3 that are close to, but lower than, the levels of c-and d-T3 found in human and animal plasma after supplementation (Lodge et al 2001;Mustad et al 2002). Furthermore, half life of all T3 investigated in humans (a, c, d) are 4.5-8.7 times shorter than those of a-TOH (Yap et al 2001;Schaffer et al 2005), thus suggesting unfavorable pharmacokinetics of oral administration protocols by sustained liver metabolism.…”
Section: Metabolite Formation and Activitymentioning
confidence: 77%
“…The lowest IC50 levels in breast cancer cells (McIntyre et al 2000) were obtained by means of days of in vitro exposure to concentrations of HM T3 that are close to, but lower than, the levels of c-and d-T3 found in human and animal plasma after supplementation (Lodge et al 2001;Mustad et al 2002). Furthermore, half life of all T3 investigated in humans (a, c, d) are 4.5-8.7 times shorter than those of a-TOH (Yap et al 2001;Schaffer et al 2005), thus suggesting unfavorable pharmacokinetics of oral administration protocols by sustained liver metabolism.…”
Section: Metabolite Formation and Activitymentioning
confidence: 77%
“…There were large differences in the antidegranulation effects of α-T3, β-T3, γ-T3, and δ-T3, with the order of the effects being δ-T3 β-T3 γ-T3 α-T3. The strength of the effect may depend on the intracellular concentration 41 and it has been reported that δ-T3 is most easily taken into cells, among the T3 isoforms 42 . Consistent with this finding, examination of the cellular uptake of each T3 isoform in the current study showed that the intracellular level of δ-T3 was especially high Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If this beneficial effect is effective in the ester analogues of T3, the analogues of T3 have a similar advantage as TS as an anticancer agent. The in vivo elimination half life of T3 is quite low compared to T, 14 however, so it is unclear whether the analogues of T3 have a beneficial effect in vivo. Moreover, because the ether bond in T3E is not subjected to enzymatic hydrolysis in vivo, the anticancer property of T3E observed in our study seems to be effective in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…12 Tocotrienols and tocopherols, collectively known as vitamin E, are lipid-soluble antioxidants. 13 The in vivo elimination half life of tocotrienols is significantly shorter than that of ␣-tocopherol (T), 14 however, indicating that the tumor-suppressive potential of tocotrienols may be largely weakened in vivo.From recent reports, it seems that the short elimination half life of tocotrienols depends on high metabolic rate and antioxidant property. 15,16 To prolong the elimination half-life and reinforce the anticancer activity of tocotrienols in vivo, it may be a useful procedure to block the antioxidant property of tocotrienols.…”
mentioning
confidence: 99%
See 1 more Smart Citation